Avaliação social baseada na classificação internacional de funcionalidade, incapacidade e saúde em crianças com paralisia cerebral - Correia, Viviane Duarte (2015)
The Cerebral Palsy (CP) is the most common cause of severe disability in childhood. Understand the circumstances in with the children with CP live is one of the premises treated in the World Report s recommendations on Disability (2012). Therefore, this study presents an analysis of the social contribution of the International Classification of Functioning, Disability and Health (ICF) in children with Cerebral Plasy. General Purpose: Know the socioeconomic and demographic universes of the children with CP based on the ICF. Specific: Detect environmental and family factors that may affect the rehabilitation process, according to the health domain of ICF; contribute to the theoretical and methodological structure of the practice of social work in rehabilitation teams of people with disabilities. Methodology: This is quantitative, qualitative and descriptive study. The subjects are 25 children and youngs, between 0 and 18 years diagnosed with CP followed by the Physical Medicine and Reabilitation Institute, Lucy Montoro Network, in the units of the southern region of São Paulo city. A family caregiver of each child with CP, was interviewed by two instruments, prepared by the researcher: Socioeconomic and demographic profile of patients with cerebral palsy; and Social Assessment based on the International Classification of Functioning, Disability and Health. Results: The survey revealed that family arrangements could interfere with treatment in children with CP. Families of children with CP, subjects of this study, have lower incomes. The support received is given by the patient s nuclear family. Most of the patients had trouble in social interactions. The housing policy showed the worst indexes, followed by education policy. For transport and health policies, there was intensity variation, however, they were assessed as facilitating the context of life of the patient. Negative attitudes of society had the lowest scores evaluation. Conclusions: The CIF represents an appropriate assessment model to obtains subsidies, that are necessary and sensitive for the analysis of human -social reality, lived by a child with CP. Furthermore, it assists in identifying disabling barriers and allows an analysis on the provision of public services